2023
DOI: 10.1186/s13002-023-00577-5
|View full text |Cite
|
Sign up to set email alerts
|

Edible wild plant species used by different linguistic groups of Kohistan Upper Khyber Pakhtunkhwa (KP), Pakistan

Abstract: Background The mountainous territory of Kohistan shelters diverse food plant species and is considered one of the important hotspots of local plant knowledge. In the era of globalization and food commodification, wild food plants (WFPs) play an important role in supporting local food systems and related local knowledge is one of the important pillars of food sustainability across the region. Since the area is populated by different cultural groups and each culture has retained particular knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…On the other hand, fruits of Ficus racemosa, Madhuca longifolia, Coccinia grandis, Neolamarckia cadamba, Ziziphus nummularia, and Artocarpus lacucha were informed as popular choices for the local people. Both the plant parts (leaves and fruits) were mostly utilized by the local tribes and in agreement with the current study, those edible parts were found as the main source of wild food in other areas of the Asian continent including India (Khan et al, 2015;Bhatia et al, 2018;Mallick et al, 2020;Cheng et al, 2022;Amin et al, 2023).…”
Section: Diversity Of Edible Partssupporting
confidence: 90%
“…On the other hand, fruits of Ficus racemosa, Madhuca longifolia, Coccinia grandis, Neolamarckia cadamba, Ziziphus nummularia, and Artocarpus lacucha were informed as popular choices for the local people. Both the plant parts (leaves and fruits) were mostly utilized by the local tribes and in agreement with the current study, those edible parts were found as the main source of wild food in other areas of the Asian continent including India (Khan et al, 2015;Bhatia et al, 2018;Mallick et al, 2020;Cheng et al, 2022;Amin et al, 2023).…”
Section: Diversity Of Edible Partssupporting
confidence: 90%
“…Our research on food ethnobotany recorded substantial body of local plant knowledge among the different ethnolinguistic groups living across the Kohistan region [ 1 ]. The current ethnobotanical survey has primarily been guided by our food ethnobotanical research work in the region.…”
Section: Introductionmentioning
confidence: 99%
“…That is why a systematic data collection from authentic and knowledge-rich person and its logical interpretation is the keys to the desired outcome of the ethno-guided study of medicinal plants which has been followed in our present study on the medicinal plant use by the Santal tribal people of Birbhum district, West Bengal. Very recently, some interesting quantitative ethnobotanical research works have carried out from India (Haq & Singh 2020, Haq et al 2022, Laldingliani et al 2022, Hassan et al, 2022, Silambarasan et al 2023) and abroad (Umair et al 2017, Huang et al 2022, Amin et al 2023, Tahor et al, 2023. However, literature survey revealed that, till date, almost all of the studies made from the state of West Bengal including Birbhum district were focused on simple documentation of plant use knowledge emphasizing floristic studies (Sur et al 1992, Mondal & Rahaman 2012, Mondal & Rahaman 2013, Pradhan & Rahaman 2014, Das & Rahaman 2014, Konar and Mondal, 2022 and a few ethnomedicinal studies with application of some statistical tools (Mandal & Rahaman 2022, Subba et al 2023.…”
Section: Introductionmentioning
confidence: 99%